SCREENING AND ASSESSMENT OF THE NUTRITIONAL STATUS IN CHILDREN IN BACH MAI HOSPITAL IN 2020 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the reality of screening and assessing nutritional status at the PediatricsDepartment of Bach Mai hospital.Methods: Design of a before-after comparison study, on a sample of 200 pediatric patientsfrom medical records from June to November 2020.Results: Pediatric patients recorded full weight, height within 36 hours after admissionincreased by 8.5% after improvement. The number of children who recorded weight and heightbefore improvement was 108, corresponding to 54.5%. The number after improvement is 195children, corresponding to 97.5%, higher than before improvement is 43%. The percentageof patients who achieved a 1-week reduction in food intake was recorded at a higher rate of19.5%. On the medical records, the medical staff recorded and weighed the children: beforethe improvement was 150 medical records, corresponding to 75%, after the improvement,187 medical records corresponding to 93.5%, 18.5% higher than before improvement. Thepercentage of children who were screened to assess their nutritional status after performingthe improved research increased to over 90%.Conclusion: Screening sheet to assess nutritional status for inpatient pediatric patientsapplied at the Pediatrics Department of Bach Mai Hospital to improve nutritional status.Medical staff follow the form with full information according to the screening sheet, effectivenutrition intervention for inpatient pediatric patients. The percentage of pediatric patientswho were screened to assess their nutritional status after improving their nutritional statusincreased to over 90% after implementing the Nutrition Status Screening Sheet.
Keywords: Nutritional screening, nutritional assessment, pediatric patients.